The role of everyday life and resistance culture in non-adoption of the internet in Greece: A qualitative examination - Panayiota Tsatsou (Questions de communication, 2010)
On the grounds of the objective of this special journal issue to focus on qualitative approaches in the analysis of ICTs’ non-users, I report on the views of internet users and non-users in Greece regarding the main reasons lying behind their decision to adopt the internet or not. The aim is to answer the question: ‘what are the main forces driving people in Greece to adopt ICTs like the internet or not?’ The methodology is focus groups, which have constituted the final phase of a mixed three-phased empirical study and have specifically followed up the second phase, a large-scale quantitative survey. The research finds that the parameters of ‘need’, ‘learning’ and ‘incentives’ are the driving forces of non-adoption of the internet in Greece. These parameters must be seen in an everyday life context, as they are intimately associated with internet non-users’ everyday lives and their priorities in life. Thus, these parameters frame non-users’ resistant attitudes to the internet and the conscious decision of non-users not to adopt the internet, while challenging arguments about exclusion and lack of access. On the other hand, users have chosen to use the internet either willingly or under pressure. In the latter case, they limit their usage severely, thus demonstrating ‘resistant’ attitudes to advanced internet usage on the basis of their circumstances, priorities and values in life. The article also makes some methodological comments concerning the ways in which the focus groups enrich, strengthen or weaken the findings that the preceding quantitative survey offered.